Is it me or is it us – Effect of agent autonomy on perceptions as a team - Müller, Rebecca; Graf, Benedikt; Ellwart, Thomas; Antoni, Conny H. (Computers in human behavior reports, 2025)
It is important to know what characteristics of agents influence human perceptions of being a team with agents. Theoretical research suggests that higher agent autonomy leads to a greater human perception of being in a team with agents. To assess this theoretical assumption, we used a within-subject experiment with ninety-four participants in this pre-registered study. We investigated whether agent autonomy (no vs. partial vs. high agent autonomy) influences human perceptions of being a team with the agent. We used different aspects of teamwork (i.e., task interdependence, role uniqueness, agent perception as team member or tool, team identity) as indicators of human perceptions of being a team with the agent. Participants perceived higher task interdependence, role uniqueness, agent perception as team member or tool, and team identity with partial compared to no agent autonomy. We found no differences between partial and high agent autonomy on indicators of human perceptions of being a team with the agent. Qualitative analyses show that from partial autonomy of the agent onwards, other factors (e.g., collaboration, anthropomorphic cues) are more important to perceive the agent more as a team member rather than simply increasing autonomy. We extend existing frameworks for human-autonomy teams beyond a sole focus on agent autonomy and objective task interdependence. •Partial agent autonomy leads to the highest perception of being a team with agents.•Agent autonomy and team perceptions follows an inverted U-curve.•Human-agent communication is more important to perceive agents as team members.•Agent autonomy is less important for human-agent teamwork than for technical issues.•Agent autonomy and automation should be better theoretically distinguished.